COMPREHENSIVE CALIBRATION AND VALIDATION SITE FOR INFORMATION REMOTE SENSING - C. R. Li; L. L. Tang; L. L. Ma; Y. S. Zhou; C. X. Gao; N. Wang; X. H. Li; X. H. Wang; X. H. Zhu (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2015)
As a naturally part of information technology, Remote Sensing (RS) is strongly required to provide very precise and accurate information product to serve industry, academy and the public at this information economic era. To meet the needs of high quality RS product, building a fully functional and advanced calibration system, including measuring instruments, measuring approaches and target site become extremely important. Supported by MOST of China via national plan, great progress has been made to construct a comprehensive calibration and validation (Cal&Val) site, which integrates most functions of RS sensor aviation testing, EO satellite on-orbit caration and performance assessment and RS product validation at this site located in Baotou, 600km west of Beijing. The site is equipped with various artificial standard targets, including portable and permanent targets, which supports for long-term calibration and validation. A number of fine-designed ground measuring instruments and airborne standard sensors are developed for realizing high-accuracy stepwise validation, an approach in avoiding or reducing uncertainties caused from nonsynchronized measurement. As part of contribution to worldwide Cal&Val study coordinated by CEOS-WGCV, Baotou site is offering its support to Radiometric Calibration Network of Automated Instruments (RadCalNet), with an aim of providing demonstrated global standard automated radiometric calibration service in cooperation with ESA, NASA, CNES and NPL. Furthermore, several Cal&Val campaigns have been performed during the past years to calibrate and validate the spaceborne/airborne optical and SAR sensors, and the results of some typical demonstration are discussed in this study.